2017
DOI: 10.1016/j.repc.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Estratificação prognóstica na hipertensão pulmonar: valor acrescido da abordagem multibiomarcadores

Abstract: A multi-biomarker approach was superior for risk stratification to any single marker. A score that incorporates NT-proBNP, MR-proANP, renin and sST2 accurately identifies patients at low, intermediate and high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Placido at el. reported increased risk of mortality for patients diagnosed with PH who have sST2 level above 68.6 ng/mL [35]. It is worth emphasizing that in our study we only analyzed early postprocedural complications and not long-term prognosis of patients with PH as conducted by Placido et al…”
Section: Discussionmentioning
confidence: 91%
“…Placido at el. reported increased risk of mortality for patients diagnosed with PH who have sST2 level above 68.6 ng/mL [35]. It is worth emphasizing that in our study we only analyzed early postprocedural complications and not long-term prognosis of patients with PH as conducted by Placido et al…”
Section: Discussionmentioning
confidence: 91%
“…These patients were followed for a mean follow-up duration of 14 months in which 12 patients experienced clinical worsening [18]. Another study found a significant association between sST2 in 43 patients with various types of PH except due to left heart disease and found higher levels of sST2 in patients who were hospitalized for heart failure or died during follow-up [19]. This is in line with our study, which demonstrated a significant association between sST2 and the transplant-free survival in a large cohort of patients with a longer follow-up duration, whom were prospectively followed since their initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…No acompanhamento de pacientes com hipertensão pulmonar, diversos aspectos são norteadores de decisões terapêuticas e determinantes do prognóstico (TORRES et al, 2015). Nos últimos anos, vários biomarcadores da HP foram investigados com o intuito de buscar um método eficiente e não invasivo de estratificação e monitorização (PLÁCIDO et al, 2017). Nos anos 1970, a oxigenação por membrana extracorpórea foi usada para administrar a insuficiência respiratória e a hipertensão pulmonar e, de certa forma, posteriormente para assistência cardíaca ventricular (KATTAN et al, 2017).…”
Section: Discussionunclassified